Concepts, Characteristics, and Scope of Arabic Curriculum Management - Ariati, Fitri; Retoliah; Zulfikri (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2025)
This study explores the fundamental concepts, key characteristics, and theoretical scope of Arabic language curriculum management within the broader context of educational management. The study is based on a library research method that analyzes relevant academic and regulatory literature. Arabic curriculum management is defined as a comprehensive, cooperative, systemic, and systematic process involving the planning, organization, implementation, and supervision of curriculum elements to achieve the goals of Arabic language education. The paper distinguishes between two dominant models of curriculum management: centralized management, in which curricular authority is held by national agencies (as exemplified by the 2013 National Curriculum), and decentralized management, in which curriculum development is delegated to individual schools (as seen in the KTSP model). Furthermore, the scope of Arabic curriculum management encompasses four core domains: curriculum planning, organizing, implementation, and evaluation. The study concludes that effective Arabic curriculum management requires the professional competence of implementers and must be responsive to both national standards and local educational needs.